A study on the factors influencing the intention to receive booster shots of the COVID-19 vaccine in China based on the information frame effect - Zhu, Qizhen; Gao, Yunyun; Hu, Qingyuan; Hu, DeHua; Wu, Xusheng (Frontiers in Public Health, 2024)
In the response to and prevention and control of the Novel coronavirus pneumonia, the COVID-19 vaccine does not provide lifelong immunity, and it is therefore important to increase the rate of booster shots of the COVID-19 vaccine. In the field of information health science, research has found that information frames have an impact in changing individual attitudes and health behaviours.Objective This study focuses on the effects of different influencing factors on the public's willingness to receive the booster shots of the COVID-19 vaccine under two information frameworks Methods An online questionnaire was conducted to explore the effects of demographic characteristics, personal awareness, social relationships, risk disclosure, perceived booster vaccination protection rate, and duration of protection under the assumption of an information framework. T test and one-way analysis were used to testing the effect of variables.(1) The persuasion effect under the gain frame is higher than that under the loss frame (B=0.863 vs B= 0.746); (2) There was no significant difference in subjects' intention of booster vaccination in terms of gender, age, income, occupation, educational background and place of residence. Whether family members received booster vaccination was strongly correlated with their intention of vaccination under the loss framework(P = 0.017, M= 4.63, SD= 0.664). (3) The higher Prior 删除[云影]: 字体: 非加粗 设置格式[云影]: This study explored the factors influencing the intention to receive COVID-19 vaccine booster shots based on information framing.The persuasive impact of the gain frame is superior to that of the loss frame, and socio-demographic factors, privacy disclosures and perceived vaccine effectiveness and duration of protectionhave an influence on individuals' willingness to receive the booster shot for the Novel coronavirus pneumonia (COVID-19).